2019
DOI: 10.1371/journal.pone.0217460
|View full text |Cite
|
Sign up to set email alerts
|

Does variability of footfall kinematics correlate with dynamic stability of the centre of mass during walking?

Abstract: A stable walking pattern is presumably essential to avoid falls. Stability of walking is most accurately determined by the short-term local dynamic stability (maximum Lyapunov exponent) of the body centre of mass. In many studies related to fall risk, however, variability of step width is considered to be indicative of the stability of the centre of mass during walking. However, other footfall parameters, in particular variability of stride time, have also been associated with increased risk for falling. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 47 publications
2
14
1
Order By: Relevance
“…BWS also reduces ML λ s pos and ML λ s vel , indicating greater local dynamic stability in the frontal plane than during free walking. Variability of step width [58] along with ML aCOM sway and its variability were also reduced, which is in line with the general belief that BWS per se already increases dynamic stability [72,77,78]. Along the sagittal plane, Kyvelidou et al found however increased λ s and kinematic variability of the hip, knee, and ankle angles during walking with BWS on a treadmill [79].…”
Section: Body Weight Support Effectssupporting
confidence: 68%
See 1 more Smart Citation
“…BWS also reduces ML λ s pos and ML λ s vel , indicating greater local dynamic stability in the frontal plane than during free walking. Variability of step width [58] along with ML aCOM sway and its variability were also reduced, which is in line with the general belief that BWS per se already increases dynamic stability [72,77,78]. Along the sagittal plane, Kyvelidou et al found however increased λ s and kinematic variability of the hip, knee, and ankle angles during walking with BWS on a treadmill [79].…”
Section: Body Weight Support Effectssupporting
confidence: 68%
“…λ s is therefore especially suitable for detecting differences between position-timing dependent systems such as COM motion while walking [ 55 57 ]. λ s can be used as a proxy measure of freedom in ML COM motion [ 58 ]. A higher λ s indicates larger chaotic elements of a system, while λ s close to zero indicates a stable system [ 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…leg retraction) to counteract terrain perturbations during running ( Muller et al, 2016 ; Seyfarth et al, 2003 ; Daley et al, 2007 ). However, reflex-mediated feedback control (of, for example, foot placement: Ignasiak et al, 2019 ; Joshi and Srinivasan, 2019 ) may be predominantly involved in locomotion at slow speeds ( Marigold and Patla, 2005 ). Furthermore, it remains unclear how these mechanisms vary across different perturbation types and sizes.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the small effect in AP mean gait stability was not different between the two walking modes. About 68% of extrapolated COM motion can be predicted using the step width and length from the current and four preceding steps [ 37 ]. Murray et al reported that during non-matched slow, preferred, and fast treadmill walking, subjects walked with shorter step lengths compared to overground [ 18 ].…”
Section: Discussionmentioning
confidence: 99%